2021
DOI: 10.1007/s11482-021-09980-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Specific Purpose Orientations in Working Adults

Abstract: The purpose of this study was to develop and validate a scale designed to measure specific purpose orientations among adults. Following literature review, a pool of items was developed and pilot tested with a convenience sample of adults recruited through MTurk (N = 554). Exploratory factor analysis suggested three distinct dimensions of others-growth, self-growth, and career-focused purpose orientations. The three-factor structure was confirmed with two independent samples of intercollegiate coaches in Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
(63 reference statements)
0
23
1
Order By: Relevance
“…The Specific Purpose Orientations of Working Adults Scale 14 is comprised of 12 items designed to measure others-growth purpose orientation (four items, e.g. My purpose in life is to make a positive impact on others ), self-growth purpose orientation (four items, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Specific Purpose Orientations of Working Adults Scale 14 is comprised of 12 items designed to measure others-growth purpose orientation (four items, e.g. My purpose in life is to make a positive impact on others ), self-growth purpose orientation (four items, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Reliability estimates were reported to be .85-.96 for others-growth purpose orientation, .84-.93 for self-growth purpose orientation, and .86-.92 for career-focused purpose orientation. 14…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purpose orientations can be described as long-term life goals in specific areas of one's life. Research has shown that the nature of purpose orientations, or major life goals, is linked with various academic and well-being outcomes (e.g., Hill et al, 2010 ; Sharma et al, 2017 , 2021 ; Yukhymenko-Lescroart & Sharma, 2021 ). For example, Sharma et al examined the role of career, interpersonal, altruistic, and self-oriented purpose orientations using the 2002 Educational Longitudinal Study database and found that (a) career purpose orientation was a positive predictor of high school graduates’ decision to apply for college ( Sharma et al, 2017 ), and (b) both career and interpersonal purpose orientations were positive predictors of college students’ postsecondary education completion a decade later ( Sharma et al, 2021 ).…”
Section: Life Purpose Orientations and Relationships With Academic E...mentioning
confidence: 99%